OP04 Synergistic influence of tapasin and HLA class I protection against chronic Hepatitis C virus infection. (6th September 2011) - Ashraf, S; Knapp, S; Becford-Tackoir, C; Brooks, C; Little, A-M; Alexander, G; Cramp, M; Khakoo, S I
Abstract : Introduction: HLA class I is associated with the outcome of hepatitis C virus (HCV) infection. Tapasin is a member of the peptide loading complex that loads self and viral peptides onto HLA class I. Presentation of viral peptides by HLA class I is critical in generating an effective cytotoxic T lymphocyte (CTL) response, and hence in clearing HCV infection. However, not all HLA alleles require tapasin for efficient peptide loading. Thus polymorphisms in the tapasin gene could affect clearance of HCV in combination with specific "tapasin-dependent" HLA class I alleles. The SNP rs2071888 is a non-synonymous polymorphism in exon 4 of the Tapasin gene causing an arginine to threonine change that could affect tapasin function. We have investigated the effect of this SNP in resolving hepatitis C virus (HCV) infection in a cohort of 336 patients from the UK. Aim: We have investigated the effect of the SNP rs2071888 in resolving hepatitis C virus (HCV) infection in a cohort of 336 patients from the UK. Method: Genomic DNA from 216 chronically infected individuals and 120 spontaneous resolvers of HCV was genotyped with an allele specific PCR designed to identify the G/C SNP in exon 4 of the Tapasin gene. Individuals were also typed for HLA-A, -B and -C. Results were analysed for association with hepatitis C outcome. Results: Overall the G allele of tapasin was associated with protection against chronic HCV infection (p=0.018, OR=1.99, 95% CI 1.14 to 3.46). Interestingly, in combination with heterozygosity at the HLA-B locus, heterozygosity at the tapasin locus was also protective (Abstract OP04 figure 1, p trend =0.005). Furthermore, we identified specific HLA-B alleles associated with protection in the context of the Tapasin G, but not Tapasin C allele. Specifically the G allele was most protective in the context of B*0702 (p=0.029, OR=4.56, 95% CI 1.2 to 17.27), and B*5701 (p=0.029, OR=12, 95% CI 1.2 to 120). Tapasin has been shown to bind specifically to amino acids 114 and 116 of HLA class I. Consistent with this functional interaction we found that aspartate at position 114 and serine at 116 were most beneficial in the context of both the G allele (D114/TapG, p<0.0001, OR=3.3, 95% CI 1.83 to 5.98; S116/TapG, p<0.0001, OR=2.73, 95% CI 1.57 to 4.76). Conclusion: The G allele of tapasin was associated with protection from chronic HCV infection, both alone and in combination with specific HLA class I alleles. Individuals who are heterozygous for both tapasin and HLA-B are relatively protected from chronic HCV infection. This heterozygosity may allow them to present a broader range of peptides to CTL and thus mount a more effective anti-HCV immune response.